2019
DOI: 10.1007/s10853-019-04099-y
|View full text |Cite
|
Sign up to set email alerts
|

Palladium nanoparticles supported on amine-functionalized alginate foams for hydrogenation of 3-nitrophenol

Abstract: A new material, consisting of alginate-polyethyleneimine (AP) foam, with high percolating properties has been designed for palladium recovery in fixed-bed reactor. The foam, having high affinity for Pd(II), can be also used for manu-facturing heterogeneous hydrogenation catalyst. SEM-EDX and TEM analyses were performed to determine the structure of the foams and the distribution of Pd nanoparticles (after metal reduction). Metal-sorbent interactions and oxida-tion state of Pd are characterized by XPS. Pd(0)-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…element appears as the bond between N and Pd (Wang et al, 2020c), further demonstrating the reaction between amine groups and chloro-anionic Pd species. It is noteworthy that a new band at 289.1 eV for C 1s appears.…”
Section: Pd Sorption Mechanismmentioning
confidence: 89%
“…element appears as the bond between N and Pd (Wang et al, 2020c), further demonstrating the reaction between amine groups and chloro-anionic Pd species. It is noteworthy that a new band at 289.1 eV for C 1s appears.…”
Section: Pd Sorption Mechanismmentioning
confidence: 89%
“…However, at low pH (pK a # pH), the neutral amino groups are protonated into ammonium (cationic (-NH 3 + )) ions, leading to electrostatic repulsion between the ammonium ions and causing the hybrid microgels to swell. 98,132,[199][200][201][202][203] Hydrogen bonding is present between the ammonium ions and water molecules, but electrostatic repulsion occurs between the ammonium ions themselves due to their like charges. Consequently, more water molecules can enter into the pores of the microgels in the cationic structure (protonated form, swelling state) compared to the neutral structure (deprotonated form, deswelling state).…”
Section: Ph Sensitivitymentioning
confidence: 99%
“…In this way, the catalytic performance as well as the adsorption capacity of microgels and hybrid microgels can be controlled by swelling and deswelling behavior. Wang et al [67] have reported the synthesis of palladium nanoparticles loaded in an alginate-polyethyleneimine A-P(EtI) crosslinked organic polymer system. The loading of palladium (II) ions is controlled by adjusting the pH of the medium.…”
Section: Cationic Microgels and Hybrid Microgelsmentioning
confidence: 99%
“…They monitored this adsorption process with a UV-visible spectrophotometer. Wang et al [67] have synthesized microgel, which is then used for the sorption of palladium ions and simultaneously for the catalytic reduction of 3NiP. The sorption of palladium ions occurs due to ion-dipole interactions.…”
Section: As Adsorbentmentioning
confidence: 99%